2015
DOI: 10.1037/ort0000057
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among victimized women on probation and parole: A latent class analysis.

Abstract: Latent class analysis was used to identify subgroups of victimized women (N=406) on probation and parole differentiated by levels of general psychological distress. The nine primary symptom dimensions from the Brief Symptom Inventory (BSI) were used individually as latent class indicators (Derogatis, 1993). Results identified three classes of women characterized by increasing levels of psychological distress; classes were further differentiated by posttraumatic stress disorder symptoms, cumulative victimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…In contrast to the findings in this study, these studies have consistently found classes that are characterized by varying levels of symptom severity, rather than distinctive symptom profiles. Studies conducted with war veterans (Armour et al, 2015) and victimized women who were on probation and parole (Golder et al, 2015) have found evidence for low, moderate and high symptoms classes. Studies conducted with sexual assault survivors (Au et al, 2013) and motor vehicle accident victims (Hruska et al, 2014) identified an additional low-moderate symptoms class, and a study conducted with adults exposed to ongoing shelling in Israel found an additional moderate-high symptoms class (Itzhaky et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings in this study, these studies have consistently found classes that are characterized by varying levels of symptom severity, rather than distinctive symptom profiles. Studies conducted with war veterans (Armour et al, 2015) and victimized women who were on probation and parole (Golder et al, 2015) have found evidence for low, moderate and high symptoms classes. Studies conducted with sexual assault survivors (Au et al, 2013) and motor vehicle accident victims (Hruska et al, 2014) identified an additional low-moderate symptoms class, and a study conducted with adults exposed to ongoing shelling in Israel found an additional moderate-high symptoms class (Itzhaky et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of SUD and PTSD can be complicated by a multitude of additional problems. Classifying 404 female probationers and parolees into three groups according to overall measures of psychological distress including mood, anxiety, and psychotic disorder symptoms, Golder, Engstrom, Hall, Higgins, and Logan (2015) reported that women in the highest distress group had the highest rates of regular use of alcohol to intoxication (70% vs. 52% of other groups). High distress was also associated with increased reports of PTSD, IPV, and other victimization, indicating the interrelation of all three phenomena with additional mental health problems.…”
Section: Substance Use Ptsd and Ipv Victimization Among Female Offementioning
confidence: 99%
“…Experiences of childhood trauma (i.e., CPA, CSA, and CEA) increase the risk for a range of negative mental health, substance use, criminological, and adult victimization outcomes (Golder, Engstrom, Hall, Higgins, & Logan, 2015; Golder et al, 2014; Johnson & Lynch, 2013; Kennedy, Mennicke, Feely, & Tripodi, 2018). Regardless of how childhood trauma is conceptually and operationally defined (e.g., singular experiences of CSA, or cumulative experiences of multi- or poly-victimization), it is significantly associated with a range of mental health issues from anxiety disorders (Lindert et al, 2014), to depression (Lindert et al, 2014), to hallucinations and psychosis (Marwaha & Bebbington, 2015).…”
Section: The Long Reach Of Childhood Trauma For Incarcerated Womenmentioning
confidence: 99%
“…These associations are amplified for incarcerated women, and estimates suggest that nearly 74% of incarcerated women meet criteria for one or more psychiatric disorders with anxiety, depression, posttraumatic stress, and psychosis being the most prevalent (Kennedy et al, 2016). Analyzing the role of anxiety, depression, and psychosis as potential variables mediating the relationship between child abuse and recidivism for women released from prison is important because literature indicates that these mental health variables are significantly associated with childhood trauma (Golder et al, 2015; Huebner, DeJong, & Cobbina, 2010; Kennedy, Tripodi, & Pettus-Davis, 2013), they disproportionately affect incarcerated women when compared with the general population (Stanton, Kako, & Sawin, 2016), and, in some cases, they directly predict recidivism (Mallik-Kane & Visher, 2008). Understanding how anxiety, depression, and psychosis intersect with childhood trauma and affect the risk for recidivism after release will guide the implementation of empirically supported interventions in the prison setting to reduce the negative impact of symptoms on women’s lives and improve their success after release.…”
Section: The Long Reach Of Childhood Trauma For Incarcerated Womenmentioning
confidence: 99%